2012
DOI: 10.1177/0013164411432166
|View full text |Cite
|
Sign up to set email alerts
|

The Rasch Rating Model and the Disordered Threshold Controversy

Abstract: The Rasch rating (or partial credit) model is a widely applied item response model that is used to model ordinal observed variables that are assumed to collectively reflect a common latent variable. In the application of the model there is considerable controversy surrounding the assessment of fit. This controversy is most notable when the set of parameters that are associated with the categories of an item have estimates that are not ordered in value in the same order as the categories. Some consider this dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
106
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 19 publications
(45 reference statements)
0
106
1
2
Order By: Relevance
“…The disordered threshold indicated issues with the discrimination of the item and could have caused problems with validity and reliability. Items with disordered parameter estimates need to be reviewed with regard to these issues (Adams, Wu, & Wilson, 2012;Andrich & Styles, 2004). This would improve the response categories conforming to the recommended Rasch Andrich thresholds even though the reliability of both person and item decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The disordered threshold indicated issues with the discrimination of the item and could have caused problems with validity and reliability. Items with disordered parameter estimates need to be reviewed with regard to these issues (Adams, Wu, & Wilson, 2012;Andrich & Styles, 2004). This would improve the response categories conforming to the recommended Rasch Andrich thresholds even though the reliability of both person and item decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The dimensionality study provided by Amburgey and Thoman (2012) found measurement issues in item 9 as well, where the item did not load as a signifi cant predictor for ecological concern in a confi rmatory factor analysis. Another hypothesis can be found in Adams, Wu and Wilson (2012), where it is discussed that the lack of frequencies in response categories within the rating scale might bias fi tting measures -and responses on lower categories were scarce for both items 3 and 9. Further investigation is needed with a balanced sample through response categories.…”
Section: Discussionmentioning
confidence: 99%
“…The ordering of the PCM's categories is independent of the ordering of the thresholds and has to be assumed prior to data analysis (Masters, 1988). For a more detailed formal treatment of the distinction between the ordering of the response categories and the ordering of the thresholds, see Adams et al (2012).…”
Section: Relationship Between Category Probabilities and Threshold Ormentioning
confidence: 99%